The Association Between Parental Smoking Habits and the Incidence of Lower Respiratory Tract Infections in Children Under Five Years of Age: A Systematic Review - Rahmi Annisa Syarli; Nurul Hikmah Amanatillah; Achmad Yudi Albari Pohan; Febi Alefiya (International Medical Journal Corp. Ltd, 2025)
Introduction: Lower Respiratory Tract Infections (LRTI), including pneumonia and bronchiolitis, represent a leading cause of morbidity and mortality in children under five years of age globally. Parental smoking, leading to environmental tobacco smoke (ETS) exposure, is a significant and modifiable risk factor. This systematic review synthesizes and critically appraises the contemporary evidence examining the association between parental smoking habits and the incidence and severity of LRTI in this vulnerable population. Methods: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, a systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for observational studies (cohort, case-control, cross-sectional) published up to July 2024. The PICO framework guided the selection of studies investigating the association between parental smoking (prenatal or postnatal) and LRTI (pneumonia, bronchiolitis, bronchitis) in children under five. The methodological quality and risk of bias of included studies were assessed using the Cochrane Risk of Bias tool for non-randomised studies (ROBINS-I). Results: Seventeen observational studies met the inclusion criteria. The evidence consistently demonstrates a significant association between parental smoking and an increased risk of LRTI. Pooled data from meta-analyses indicate that smoking by any household member increases the overall risk of LRTI by approximately 54% (OR=1.54, 95% CI 1.40–1.69). Postnatal maternal smoking was identified as the most potent risk factor (OR=1.58, 95% CI 1.45–1.73), exceeding the risk from paternal smoking alone (OR=1.22, 95% CI 1.10–1.35). The association was strongest for bronchiolitis, with household smoking increasing the risk by 151% (OR=2.51, 95% CI 1.96–3.21). Furthermore, exposure was linked to increased disease severity, including a higher likelihood of hospitalization, intensive care unit admission, and need for mechanical ventilation. A clear dose-response relationship was observed, with risk escalating with the number of smokers in the household and the proximity of smoking to the child. Discussion: The consistency of findings across diverse geographical settings and study designs, supported by strong biological plausibility, substantiates a causal relationship. Prenatal exposure appears to impair lung development, creating a congenital vulnerability, while postnatal exposure acts as a direct inflammatory trigger, impairing mucociliary clearance and immune function. The disproportionately high risk associated with maternal smoking is likely attributable to the greater time mothers typically spend in close proximity to their infants. Conclusion: There is robust and conclusive evidence that parental smoking is a major preventable cause of LRTI incidence and severity in children under five. The findings underscore the urgent need for targeted public health interventions that promote smoking cessation among parents and establish completely smoke-free home environments to protect vulnerable children.